PRODUCTIVITY OF SORGHUM (Sorghum bicolor L.) UNDER INCORPORATED LEGUMES AND NITROGEN FERTILIZATION IN SEMI-ARID ENVIRONMENT - Adesoji, Aderemi; Ogunwole, J. O.; Ojoko, E. A. (FUDMA JOURNAL OF SCIENCES, 2023)
Sustainable crop production can be achieved in a cropping system that facilitates a renewable source of nutrients for sustainable soil fertility and productivity. The study was carried to evaluate the influence of incorporated legumes and nitrogen application on productivity of sorghum (Sorghum bicolor L.). Field experiments were carried out in the wet seasons of 2015 and 2016 at the Research Farm of Federal University Dutsin-Ma, Nigeria. The treatments consisted of four levels of N (0, 30, 60 and 90kg N ha -1), and four legumes (Lablab (Lablab purpureus), Mucuna (Mucuna pruriens), Soybean (Glycine max L. Merrill), and Cowpea (Vigna unguiculata L.)) and no legume. SAMSORG 40 variety was used in this experiment. The experiment was laid out in a randomized complete block design and replicated three times. Nitrogen application significantly (P
Keywords: Incorporation, Legume, Nitrogen, Sorghum, grain yield.